'Our Clown': European Memory and Sentimental Nationality in Charlie Rivel's Unexpected Itinerary. Issue 1 (2nd January 2017) - Linhard, Tabea Alexa
Abstract: This article traces the unexpected itinerary of Catalan-born circus artist Charlie Rivel [ née Josep Andreu i Lasarre] (1896–1983) in order to address the ways in which his story conjures up the complex set of relationships that inform Catalonia's position vis-à-vis a European culture of memory. Rivel became a star of the variety and circus circuit in Europe in the 1920s and 1930s. Already famous in Germany decades before the outbreak of war, the clown performed in sold-out theatres in Berlin from 1941 to 1944. Conjectures about the dilemmas that Charlie Rivel faced in Nazi-ruled Berlin have become the basis for Gerard Vázquez's play Uuuuh! (2005) and Eduard Cortés' feature film, based on the play, El pallasso i el Führer (2007) . My reading of both texts shows that an engagement with the memory of the Holocaust is an important component of the Catalan identification and integration processes within a unified Europe. Charlie Rivel's personal, cultural and professional itineraries are inexorably linked to the ways in which the memory of World War II and the Holocaust continues to unfold today.